IMPLEMENTASI MEDIA KOMIK DALAM PEMBELAJARAN UNTUK MENINGKATKAN MOTIVASI BELAJAR SISWA - Nur Mazidah Nafala (UNZAH Genggong, 2022)
The role of comic media in learning plays a key role in increasing student motivation. The purpose of this article is to know how implementation and media functions in improving student study motivation. By using previous research for later analysis. For this reason, it is felt that educators know the benefits and implementation of comic media as learning medium so that learning is not monotonous and tend to bore students. Comics as role media are a tool that performs a learning message. In this context, learning points to a communication process between learners and learning resources (study comics). Learning communication works best when the message of learning is conveyed clearly, by blocks, and by appeals. Keyword: comics media, Learning, Education,